Comprehensive prognosis assessment of cardiovascular magnetic resonance parametric mapping in light chain amyloidosis - Xiao Li; Yubo Guo; Kaini Shen; Sisi Huang; Yajuan Gao; Lu Lin; Jian Wang; Jian Cao; Xinxin Cao; Zhengyu Jin; Zhuoli Zhang; Akos Varga-Szemes; et al. (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Recent evidence underscores the importance of cardiovascular magnetic resonance (CMR) in light chain amyloidosis (AL amyloidosis). We aimed to comprehensively assess the prognostic significance of CMR parametric mapping in AL amyloidosis. Methods: This prospective study consecutively included AL amyloidosis patients who underwent CMR imaging before therapy. The statistical analyses included T2, extracellular volume, and native T1 as variates under investigation, adjusted for well-established prognostic markers. The outcome was death from any cause. Results: In total, 195 patients (age, 57.2 ± 9.1 years; male/female, 123/72) were recruited. At the median follow-up time (19 months), the survival probability was approximately 67.2% (131/195). T >44 ms, extracellular volume fraction (ECV) >47%, and native T1 >1468 ms were significantly prognostic (all, P < 0.05) but non-significant after adjustment for N-terminal pro-B-type natriuretic peptide (all, P > 0.05) in AL amyloidosis. T2 >44 ms was independently prognostic after correcting for left ventricle (LV) late gadolinium enhancement, LV ejection fraction, LV longitudinal strain, and therapeutic response (all, P < 0.05). In patients achieving deep hematologic response, T2 >44 ms (hazard ratios [HR] 6.611, 95% confidence interval [CI] 1.723–25.361, P = 0.006) was significantly prognostic for mortality after adjustment for cardiac response. Accordingly, T2 >44 ms was significantly associated with mortality (HR 5.734, 95% CI 1.189–27.656, P = 0.030) and remained independently prognostic after correcting for LV late gadolinium enhancement and LV longitudinal strain (both, P < 0.05) in patients who achieved both deep hematologic response and cardiac response. Conclusion: This study highlights that T2 is a valuable independent predictor of mortality in an AL amyloidosis population, additive to common CMR risk factors. Moreover, myocardial edema assessment identified patients in need of adjunctive therapies, which is of particular prognostic significance in patients with deep therapeutic response.